Poststrukturalismus. Gesellschaft. Kritik: Über Potenziale, Probleme und Perspektiven - van Dyk, Silke (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2012)
In light of a boom of radical social critique following the financial crisis, Cultural Studies and poststructuralism, which used to be favorites among many left-wing academics until recently, seem to have lost ground: In the wake of the “big crisis” with its material problems and consequences, the theoretical problematization of The Subject, truth, and structure, as well as the focus on subversive micropolitics (instead of macro analyses), complex power relations and battles of interpretation is considered to be outdated and misleading. This article takes the wide-spread unease with regard to poststructuralism’s potential for radical social critique seriously and confronts the paradigm with questions concerning criticism and truth, inequality and authority and its ability to problematize society on a systemic level. The main argument is that current shortcomings in the field of radical social critique can be conquered by key ideas of poststructuralist thinking itself.